Monoclonal antibodies to dynein subunits reveal the existence of cytoplasmic antigens in sea urchin egg (The Rockefeller University Press, 1984)
Monoclonal antibodies directed against subunits of a sea urchin flagellar dynein were used to test for the presence of cytoplasmic antigens in preparations of fertilized eggs and mitotic apparati . A 9- 10 S complex composed of 330,000-, 134,000-, and 126,000-mol-wt subunits was isolated from outer arms of Strongylocentrotus purpuratus sperm flagella and used to characterize the antibodies. Seven monospecific antibodies to the 330,000 subunit and two against the 134,000 subunit of the 9-10 S complex were identified by binding to nitrocellulose blots of electrophoretograms resolving polypeptides from different dynein preparations. The antibodies were applied also to blots of polypeptides from fertilized sea urchin egg at the first metaphase and a cellular fraction of mitotic apparati . Three of the antibodies to the 330,000 subunit bound to a cytoplasmic polypeptide of approximately the same molecular weight and the two antibodies to the smaller subunits recognized a polypeptide of 124,000 apparent molecular weight. Both antigens appeared to be enriched in the fraction containing mitotic apparati . These results indicate that polypeptides similar to two subunits of the 9-10 S complex are present in eggs at metaphase, and they are apparently associated with the mitotic apparatus.